Bibliometric Analysis of Sustainable Human Resource Management - Loso Judijanto (West Science Journal Economic and Entrepreneurship, 2026)
Sustainable Human Resource Management (SHRM) has emerged as an increasingly important area of research in response to growing global concerns regarding sustainability, environmental responsibility, and long-term organizational performance. This study aims to examine the development, intellectual structure, and research trends within the field through a bibliometric analysis approach. Bibliographic data were collected from the Scopus database and analyzed using bibliometric indicators and network visualization techniques through VOSviewer. The analysis includes publication trends, co-authorship networks, institutional collaboration, country collaboration, keyword co-occurrence, overlay visualization, density visualization, and citation analysis to identify the dominant themes and emerging directions of the field. The findings indicate that research in this area is strongly centered on the concepts of sustainable development and sustainability, which function as the primary foundations connecting multiple research streams. Collaboration patterns reveal that scholarly production is concentrated among several influential authors, institutions, and countries, with strong international connectivity but uneven distribution of research leadership. Keyword mapping demonstrates that the field has evolved from an initial emphasis on environmental protection, ecosystem management, and resource governance toward a more integrated perspective incorporating decision-making processes, organizational sustainability, and human resource management dimensions. Citation analysis further shows that the intellectual foundation of the field is dominated by highly influential studies addressing food security, social-ecological systems, biodiversity conservation, climate adaptation, and sustainable resource management. Despite increasing attention to management-related topics, human resource management remains relatively underrepresented, indicating opportunities for future research. This study contributes by providing a systematic overview of the knowledge landscape and identifying potential directions for advancing Sustainable Human Resource Management research.